ESTETIKA PERTENTANGAN DALAM PUISI-PUISI BALAI PUSTAKA - Ruli Andayani; Indra Mardiyana (Universitas Negeri Makassar, 2025)
This research aims to describe the aesthetics in Indonesian poetry of the balai pustaka period. The research method used is descriptive-qualitative. The data and data sources are the words (diction) in the poetry of Indonesian poets from the balai pustaka period, namely Mohamad Yamin, Sanusi Pane, and Rustam Effendi. The data collection technique is done through literature study. Data analysis was carried out in three stages, (1) identifying elements that contribute to building the aesthetic concept; (2) identifying elements that are emphasized; and (3) concluding the harmony between aesthetic elements in forming a unity of meaning. The results of the data analysis state that balai pustaka poetry attempts to deny the aesthetics of classical poetry, both in terms of form, content, and language. The form of poetry is more dynamic and not bound by the number of stanzas, arrays, and syllables. The substance of the content emphasizes more on colonialism, politics, socio-cultural issues, and expressions of the soul towards the environment. The language used is more expressive and explores rhetorical devices, but is still influenced by poetry and rhyme.